Event Rate of Fast Radio Bursts from Binary Neutron Star Mergers - Zhi-Lin Chen; Rui-Chong Hu; Da-Bin Lin; En-Wei Liang (The Astrophysical Journal, 2023)
It is proposed that a one-off fast radio burst (FRB) with periodic structure may be produced during the inspiral phase of a binary neutron star (BNS) merger. In this paper, we study the event rate of such kind of FRB. We first investigate the properties of two one-off FRBs with periodic structure (i.e., FRB 20191221A and FRB 20210213A) in this scenario, by assuming a fast magnetosonic wave is responsible for their radio emission. For the luminosities and periods of these bursts, it is found that for the NSs in the premerger BNS, magnetic field strengths of B ≳ 10 ^12 G are required. This is relatively high compared with those of most of the BNSs observed in our Galaxy, of which their magnetic fields are around 10 ^9 G. Since the observed BNSs in our Galaxy are binaries that have not suffered a merger, a credible event rate of BNS-merger-originated FRBs should be estimated by considering the evolution of both the BNS systems and their magnetic fields. Based on population synthesis and adopting decaying magnetic fields of the NSs, we estimate the event rate of BNS mergers relative to their final magnetic fields. We find that rapidly merging BNSs tend to merge with high magnetization, and the event rate of BNS-merger-originated FRBs, i.e., BNS mergers with both NSs’ magnetic fields being higher than 10 ^12 G, is ∼8 × 10 ^4 yr ^−1 (19% of all BNS mergers) for redshifts z < 1.